2015
DOI: 10.3892/or.2015.3942
|View full text |Cite
|
Sign up to set email alerts
|

Cantharidin inhibits cell proliferation and promotes apoptosis in tongue squamous cell carcinoma through suppression of miR-214 and regulation of p53 and Bcl-2/Bax

Abstract: Cantharidin, a type of terpenoid, is a chemical compount secreted by the blister beetle or Mylabris phelarata pallas of the Meloidae family. Cantharidin is known to have good antitumor activity. The present study aimed to investigate the anticancer effect of cantharidin and its possible underlying mechanism using tongue squamous cell carcinoma (TSCC) TCA8113 cells. TCA8113 cells were treated with various concentrations of cantharidin, and the cell viability and cytotoxicity were assessed using MTT and LDH assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Based on previous findings of cantharidin as the active constituent of the Chinese medicine Mylabris (8,1012,14,15,17,20), the possible therapeutic values of cantharidin against breast cancer and underlying pathways associated with this anticancer activity were investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous findings of cantharidin as the active constituent of the Chinese medicine Mylabris (8,1012,14,15,17,20), the possible therapeutic values of cantharidin against breast cancer and underlying pathways associated with this anticancer activity were investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cantharidin has received sudden research expansion and has become a major focus in anticancer research. The latest studies have found that cantharidin and its derivatives have potent anticancer activities in various types of cancer, such as hepatoma (9), lung cancer (10), gastric cancer (11), pancreatic cancer (8,12,13), bladder cancer (14,15), epidermoid carcinoma (16), and tongue squamous cell carcinoma (17). Clinical trials have inspiringly shown that cantharidin and its analogs have therapeutic effects against primary hepatoma and advanced stage cases (7,18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of miR-214 is deregulated in many tumours including pancreatic cancer, melanoma, and hepatocellular carcinoma (Zhang et al , 2010; Penna et al , 2013; Zhang et al , 2015), whereas upregulated in breast cancer by targeting p53 (Wang et al , 2015). The pleiotropic and tumour-specific of miR-214 contributes to various cancer formation and progression via its several target genes including p53 , Bcl-2/Bax , TFAM , EZH2 (Wen et al , 2014; Yang et al , 2014; Tian et al , 2015). Recently, Chen et al (2014) reported that miR-214 negatively regulated liver metastasis in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CTD induced G2/M cell cycle arrest and apoptosis in human pancreatic cancer cells, melanoma cells, and colorectal cancer cells (Hsiao et al, 2014; Huang et al, 2011; Li et al, 2010). CTD also inhibited cell growth and promoted mitochondria-dependent apoptosis in cancer cells (Hsia et al, 2014; Kuo et al, 2010; Tian et al, 2015). CTD exerted its anti-tumor effect through inducing DNA damage and inhibiting DNA repair associated proteins in human lung cancer cells, NCI-H460, and human bladder cancer cells (Hsia et al, 2015; Kuo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%